MESOZOIC MAGMATISM IN THE FALKLAND ISLANDS (SOUTH ATLANTIC) AND THEIR OFFSHORE SEDIMENTARY BASINS. (20th December 2012) - Richards, P. C.; Stone, P.; Kimbell, G. S.; Mcintosh, W. C.; Phillips, E. R.
<x xml:space="preserve">Abstract</x> Recent mineral and hydrocarbons exploration in and around the Falkland Islands has provided data that allows correlation of the onshore and offshore histories of magmatism. New Ar‐Ar age dating of onshore dykes in East Falkland has extended their Cretaceous age range back to ca. 135 Ma (Valanginian – Hauterivian) from the previously reported age of ca. 121 Ma (Aptian). Widespread onshore, ca.188–178 Ma, Jurassic dykes are generally considered a part of the regional Karoo‐Ferrar magmatism linked to the initial break‐up of Gondwana, but we relate the Early Cretaceous dykes, with their characteristic north‐south orientation, to extension of the Falklands Plateau during initiation of spreading in the South Atlantic Ocean. The onshore dykes demonstrate east‐west Early Cretaceous extension, whilst to the north of the archipelago the offshore North Falklands Basin extended between north‐south boundary fault systems from the Late Jurassic onwards. Intrusion of Valanginian – Hauterivian dykes onshore was penecontemporaneous with the intrusion of sills and the extrusion of lavas in the Falkland Plateau Basin. This magmatism, more extensive than previously supposed, may be linked to regional uplift associated with initial opening of the South Atlantic Ocean. The uplift can be demonstrated from seismic data and DSDP boreholes to have occurred during the Berriasian – Hauterivian interval. The thermally‐driven uplift of the platform region played a crucial role in elevating potential sediment source areas and providing the large volumes of sand that were shed intermittently into the surrounding basins from the Valanginian to the Aptian or Albian.